Odpowiedzi

Najlepsza Odpowiedź!
2010-03-16T13:29:48+01:00
A) x+7=10
x=10-7
x=3
B) x-1=6
x=6+1
x=7
C) 3x+6=9
3x=9-6
3x=3 |:3
x=1
D)5=3+7x
5-3=7x
2=7x |:7
2/7=x
E)3x+5=2x
3x-2x=-5
x=-5
F)x=-2x
3x=0 |:3
x=0
G)4-x=1,3
4-1,3=x
2,7=x
H) -x-3=x-4
1=2x |:2
x=1/2
i) 8,3-3x=0,5
8,3-0,5=3x
7,8=3x |:3
x=2,6




























1 5 1
2010-03-16T13:43:51+01:00
X+7=10
x = 10 -7
x = 3

x-1=6
x = 6+1
x =7

3x+6=9
3x = 9-6
3x = 3 /:3
x = 1

5=3+7x
3 + 7x = 5
7x = 5-3
7x = 2 /:7
x = 2/7

3x+5=2x
3x - 2x = -5
x = -5

x=-2x
x + 2x = 0
3x = 0 /:3
x = 0

4-x=1,3
-x = 1,3 - 4
-x = -2,7 / x(-1)
x = 2,7

-x-3=x-4
x -4 = -x - 3
x - (-x) = -3 + 4
x + x = 1
2x = 1 /:2
x =1/2

8,3-3x=0,5
-3x = 0,5 - 8,3
-3x = -7,8 /:(-3)
x = 7,8 : 3
x =78/10 x 1/3
x =26/10
x = 2,6